The Routledge Handbook of Differentiation in the European Union. - Leruth, Benjamin. (Routledge International Handbooks Series, 2022)
The Routledge Handbook of Differentiation in the European Union offers an essential collection of ground-breaking chapters reflecting on the causes and consequences of this complex phenomenon.